2020
DOI: 10.1186/s12984-020-00694-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional movement assessment by means of inertial sensor technology to discriminate between movement behaviour of healthy controls and persons with knee osteoarthritis

Abstract: Background: Apart from biomechanical alterations in movement patterns, it is known that movement limitations in persons with knee osteoarthritis (PwKOA) are related to an individual's perception and belief regarding pain and disability. To gain more insights into the functional movement behaviour of PwKOA in a clinical setting, inertial sensor technology can be applied. This study first aims to evaluate the ability of inertial sensors to discriminate between healthy controls (HC) and PwKOA. Secondly, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Knee joint mobility is crucial in the elderly for maintaining functional independence. In subjects with KOA, specific movements in flexion and rotation cause increased pain levels [ 11 ]. This increased pain on movements causes fear of movement, and the individuals will tend to avoid these movements [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knee joint mobility is crucial in the elderly for maintaining functional independence. In subjects with KOA, specific movements in flexion and rotation cause increased pain levels [ 11 ]. This increased pain on movements causes fear of movement, and the individuals will tend to avoid these movements [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings also suggested that the IMU system could be employed to quantify upper limb movements. However, to the best of our knowledge, there has been limited information available about the system’s performance in 3D joint kinematic measurements when evaluating a wider range of motion and more complex motion tasks, such as gait (GA), squat (SQ), single-leg squat (SLS), forward lunge (FL), side lunge (SL), and counter-movement jump (CMJ), which are essential for patients with lower extremity dysfunction, especially osteoarthritis [ 25 ]. Secondly, the reliability of the IMU system in measuring human motion has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Straaten et al, 2020 [29] Knee OA individuals had more lateral trunk lean toward contralateral leg and more hip flexion throughout performance of unipodal stance task 15 IMU b (MVN BIOMECH Awinda) on entire body Healthy (n=12) and knee OA (n=19) Van der Straaten et al, 2020 [30] a OA: osteoarthritis. b IMU: inertial measurement unit (with accelerometer, gyroscope, and magnetometer).…”
Section: Assessment Of Oa Presence and Severitymentioning
confidence: 99%
“…In addition to walking, IMUs were used to compare movement patterns during other daily activities between individuals with OA and controls. In 2 studies from the same cohort of people with end-stage knee OA and controls, van der Straaten et al [29,30] compared movement patterns during various activities, including walking, lunge, stair climbing, squatting, sit-to-stand, and single-leg balance. They reported differences in multiple measures, including those representing motions of the trunk and pelvis, which had not been previously reported.…”
Section: Assessment Of Oa Presence and Severitymentioning
confidence: 99%